Analysis of social behavior and communication strategies in Women’s Bathing, Washing, and Toileting (MCK) activities in the open Aek Pohon River, Pidoli Dolok Subdistrict - Sahara Nurfitri Nasution; Marlina Marlina; Hafsah Juni Batubara (Privietlab, 2026)
This study analyzed the behavior of women who perform bathing, washing, and toileting (MCK) activities in the open Aek Pohon River in the Pidoli Dolok Subdistrict. The aim is to identify the causes, impacts, and appropriate environmental communication strategies. This study employed a qualitative method with a case study approach through observation and interviews. The results show that this behavior is influenced by limited facilities, long-standing traditions, and the perception of the river as the primary water source. Communication strategies are implemented through educational efforts, the involvement of religious leaders, and the provision of MCK facilities by the government. These findings are expected to contribute to studies on social behavior and environmental communication.